Broncho‐alveolar lavage in patients with acute respiratory distress syndrome due to COVID‐19. Issue 6 (21st June 2021) - Cornelissen, Christian G.; Bergs, Ingmar; Müller, Annegret G.; Daher, Ayham; Kersten, Alexander; Balfanz, Paul; Lemmen, Sebastian; Marx, Gernot; Marx, Nikolaus; Dreher, Michael; Müller, Tobias
Abstract: As data about microbiological testing and the cellular composition of the broncho‐alveolar lavage (BAL) fluid in patients ventilated due to coronavirus disease 2019 (COVID‐19) are lacking, this was investigated in a retrospective analysis ( n = 58). Co‐infection with pathogens was detected in 31 patients, whereas the analysis of BAL cellularity showed an increased total cell count and an alveolitis dominated by neutrophils. None of the physicians performing bronchoscopies in COVID‐19 patients had serological evidence of severe acute respiratory syndrome coronavirus 2 infection.